Orientación vocacional e intereses profesionales de los estudiantes de tercero de Bachillerato General Unificado, Unidad Educativa Particular Nuevo Ecuador, período 2024-2025 - Jiménez Coello, Camila Salomé (2025)
The purpose of this curricular integration work was to describe the vocational guidance process carried out on third-year students of Unified General Baccalaureate of Nuevo Ecuador High School; therefore, it was a qualitative, descriptive research, with a non-experimental design and a cross-sectional approach. For data collection, an interview was applied to the Student Counseling Department (DECE) and an observation form was used, applied to both the DECE and all students of the aforementioned educational level. The findings revealed that the vocational guidance process carried out by the DECE begins with the realization of workshops, where students participate in a variety of activities with the purpose of breaking with their limiting beliefs, knowing themselves and exploring their professional interests. In addition, it was identified that the pillars of this process are self-knowledge and information, since it was evident during the observation that the professional responsible for the workshop informed the students about the importance of vocational guidance and its functions during the accompaniment process. Finally, it was concluded that students express their professional interests, since during the activities they pointed out their areas of interest, the most notable being those related to health science and exact sciences